Theoretical Preconditions for Leadership of the Head of a Pre-School Education Institution - Dambrauskienė, Dalia (Jaunųjų mokslininkų darbai, 2016)
The concept of leadership and theoretical preconditions for leadership of the head of a pre-school education institution in scientific literature and legislative acts are provided in the paper. In the 21st century all institutions underwent tranformation, change has become a continuous process. That is determined by social and economic changes in society, rapid science and technology development. Changes in society, the role of leadership, management competences in education community and an institution are the issues highlighted in European and Lithuanian strategic and education policy documents. Such changes as a new style of leadership, community involvement in decision-making, implementation of shared decisions, revision and implementation of education programmes are inevitable in pre-school education institutions taking into account that the legislative framework of pre-school education has been changed. When analyzing leadership issues Lithuanian and foreign researchers focus on leadership in general education schools. A review of research carried out in Lithuania and abroad into leadership in the education sector showed that leadership in pre-school education institutions and such issue as coherent leadership at individual, institutional and communal levels.have been little researched.